Visual Field Testing in Pediatric Patients - Heidary, Gena (Journal of Pediatric Neurology, 2017)
Diseases that affect vision in pediatric patients may impair central vision (i.e., 20/20 vision) or may affect peripheral or side vision. Although there are established quantitative methods to accurately evaluate central vision throughout childhood, methods of quantifiable peripheral vision or visual field testing are more limited. Some children may be unable to cooperate or understand the methodology of conventional techniques such as automatic static perimetry used in adult patients. Despite this limitation, assessment of visual fields in pediatric patients is clinically relevant in many ophthalmologic and neurologic disease processes that affect children. The purpose of this paper is to review recent literature that examines the feasibility for formal visual field analysis in children and to provide a summary of recent efforts to develop visual field analysis tools for infants, toddlers, and children who are otherwise unable to participate using conventional visual field techniques.
Keywords: visual fields in children; Goldmann kinetic perimetry; automated static perimetry in pediatric patients